Redevelopment on the periphery: An examination of the changing status of Armadale within successive strategic plans for Perth and corresponding revisions to local planning schemes - Luscombe, Simon David (Curtin University, 2015)
This study explored the current status of Armadale, a relatively low socio-economic peri-urban settlement in Perth, Western Australia. The study analysed recent redevelopment trends resulting from a new local planning scheme and examined Armadale’s representation within consecutive strategic plans for Perth since 1955. In the absence of strong planning controls, it was found that much redevelopment in the locality continues to reflect poor built form standards.